Spleen tyrosine kinase inhibitors disrupt human neutrophil swarming and antifungal functions - Alex Hopke; Adam L. Viens; Natalie J. Alexander; Seok Joon Mun; Michael K. Mansour; Daniel Irimia (Microbiology Spectrum)
ABSTRACT Neutrophils communicate with one another and amplify their destructive power through swarming, a collective process that synchronizes the activities of multiple neutrophils against one target. The sequence of activities contributing to swarming against clusters of fungi has been recently uncovered. However, the molecular signals controlling the neutrophils’ activities during the swarming process are just emerging. Here, we report that spleen tyrosine kinase (SYK) inhibitors severely impair neutrophil swarming responses, resulting in the complete loss of fungal restriction. These findings are enabled by a microscale platform to probe the biology of human neutrophils swarming against uniformly sized clusters of growing Candida albicans, a representative opportunistic fungal pathogen. We take advantage of the ability to monitor large arrays of swarms and quantify the effect of multiple chemical inhibitors on different phases of human neutrophil swarming. We show that inhibitors that interfere with PI3Ky signaling disrupt the regulation of the initiation of swarming, while the activation of JNK signaling is essential for the activation of biochemical antifungal functions. Furthermore, we reveal that granulocyte colony-stimulating factors (GCSF and GM-CSF) can partially rescue the antifungal functions of neutrophils exposed to SYK inhibitors. These findings advance our understanding of neutrophil swarming biology in humans and lay the foundation for novel therapeutics that may restore neutrophil function during immunosuppression.IMPORTANCENeutrophils can amplify their destructive power through swarming, a crucial process against large targets that individual neutrophils cannot destroy. However, the molecular mechanisms controlling this process are just emerging. Here, we leveraged microscale tools to probe the biology of swarming against fungi. We used multiple chemical inhibitors and mapped SYK, PI3Ky, and JNK signaling roles during human neutrophil swarming against fungal clusters of Candida albicans. We also found that treating human neutrophils with GCSF and GM-CSF rescues some neutrophil antifungal function during SYK inhibition. These findings advance our understanding of swarming biology in humans while laying the foundation for developing therapeutics that enhance neutrophil function during immunosuppression.